Austerity, Localism, and the Possibility of Politics: Explaining Variation in Three Local Social Security Schemes Between Elected Councils in England. (June 2022) - Hick, Rod
The Conservative-Liberal Democrat coalition government abolished the Discretionary Social Fund and Council Tax Benefit in the Welfare Reform Act 2012 as part of their programme of austerity, with powers to design replacement schemes devolved to local authorities in England. Discretionary Housing Payments, which had long been the responsibility of local authorities, were given an expanded role – to soften the edges of welfare reform being pursued by central government. This article presents analysis of a new quantitative dataset constructed by the author detailing variations in these three payments across local authorities in England. This analysis explores the variation in provision that now exists across England and examines the extent to which the political makeup of elected councils, as well as economic and demographic differences, can explain the variations in provision that now exist. We find that there has been substantial retrenchment in the local social security schemes in the period since their localisation, indicating that the devolution of powers alongside budget cuts has proved a successful mechanism for implementing austerity. We also find that the political makeup of elected councils is associated with the degree of cutbacks in these schemes, with Labour-led councils less likely to retrench across all three payments when compared with councils led by the Conservative party, suggesting that politics remains possible even in a harsh financial climate such as that faced by local authorities in England.